Privatisation around the world: New evidence from panel data - Bernardo Bortolotti; Marcella Fantini; Domenico Siniscalco (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper presents new evidence about privatisation processes and their determinants from a panel of 34 countries over the 1977-99 period. The empirical analysis shows that privatisation takes place typically in wealthy and democratic countries, endowed with deep and liquid stock markets, and is affected by the governing political majority and public sector budget constraints. But the extent of privatisation in terms of revenues and stakes sold appears more limited in civil law countries, where shareholders are poorly protected, banks powerful, and capital markets less developed.
Keywords: L33; D72; G15; H6; K22; 330; Privatisation; public finance; political economy; law and finance; capital markets; Privatisierung; Institutionelle Infrastruktur; Neue politische Ökonomie; Schätzung; Welt